THE IMPACT OF HOAX ON COVID-19 VACCINATION IN INDONESIA - Clarissa Evangelina Hartono; Laura Tresia; Veronica Augie Nathania; Moses Glorino Rumambo Pandin (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The world is currently facing the COVID-19 pandemic and it has become easy to spread hoaxes on the internet. However, there are no papers that talk about its impact on COVID-19 vaccination. This study aims to investigate the impact of the spread of false news on the COVID-19 vaccination in Indonesia. An online survey with 396 respondents was done to investigate the frequency of COVID-19 vaccination news encounter and the trust towards the news. 17 of the respondents were then invited to an interview. The findings showed that 43.7% of the respondents are almost always exposed to news about COVID-19 vaccination and 28.7% almost always believed it. These news have created concerns, misunderstandings and noise, delaying COVID-19 vaccination in Indonesia. It is recommended to prepare more in-depth questions to be asked to respondents and conduct a longer survey. This study needs more respondents to have more validated generalization.